Bioaccessibility of Carotenoids and Tocopherols in Marine Microalgae, Nannochloropsis sp. and Chaetoceros sp. - L. P., Goh; S. P., Loh; M. Y., Fatimah; K., Peruma (Nutrition Society of Malaysia, 2009)
Microalgae can produce various natural products such as pigments, enzymes, unique fatty acids and vitamin that benefit humans. The objective of the study is to study the bioaccessibility of carotenoids (β-carotene and lycopene) and vitamin E (α- and β- tocopherol) of Nannochloropsis oculata and Chaetoceros calcitrans. Analyses were carried out for both the powdered forms of N. oculata and C. calcitrans, and the dried extract forms of N. oculata and C. calcitrans. In vitro digestion method together with RP-HPLC was used to determine the bioaccessibility of carotenoids and vitamin E for both forms of microalgae. Powdered form of N. oculata had the highest bioaccessibility of β-carotene (28.0 ± 0.6 g kg-1), followed by dried extract N. oculata (21.5 ± 1.1 g kg-1), dried extract C. calcitrans (16.9 ± 0.1 g kg-1), and powdered C. calcitrans (15.6 ± 0.1 g kg-1). For lycopene, dried extract of N. oculata had the highest bioaccessibility of lycopene (42.6 ± 1.1 g kg- 1), followed by dried extract C. calcitrans (41.9 ± 0.6 g kg-1), powdered C. calcitrans (39.7 ± 0.1 g kg-1) and powdered N. oculata (32.6 ± 0.7 g kg-1). Dried extract C. calcitrans had the highest bioaccessibility of α-tocopherol (72.1 ± 1.2 g kg-1). However, β-tocopherol was not detected in both dried extract and powdered form of C. calcitrans. In conclusion, all samples in their dried extract forms were found to have significantly higher bioaccessibilities than their powdered forms. This may be due to the disruption of the food matrix contributing to a higher bioaccessibility of nutrients shown by the dried extract forms